Apresentações e aplicações dos números complexos - Passos, Steve Uchôa (2018)
Mathematics has always been challenging. From the beginnings of science, many thinkers and scholars have spent much of their time solving mathematical problems. The more answers they got, the more they went after new questions. This curiosity brought great discoveries and, consequently, many changes that reverberated throughout history. Among the various subjects that make mathematics fascinating, in this work we will be concerned with studying the complex numbers and some of their applications. We will see the definition, the operations and their properties, the representations and the use of the complexes to solve problems. The prior knowledge of the set of real numbers ℝ and their operations as a body, the graphical representation of ℝ², the operations between matrices, the behavior of the trigonometric functions and the tools of the calculation, form the minimum necessary for the complete understanding of this dissertation.